Comparison between infiltration and inferior alveolar nerve block anesthesia for extraction of Advance periodontitis of mandibular molars - Muhammad Mubashirul Haque; Mostafa Md Anisuzzaman; Sajid Hasan; Nubad Adnan (Update Dental College, 2020)
Aim: The focus of the education was to assess the success between localanesthetic infiltration injection and inferior alveolar nerve block anesthesia in extraction of Chronic periodontitis mandibular posterior teeth. Methods: 100 patients aged between 13 and 73 years who attended the Department of Dental surgery, BIRDEM General Hospital for extraction of advance periodontitis of mandibular molars were included in this study. For the infiltration anesthetic technique, patient's approval was taken. The patients were equally divided into two groups. Group (1) received 0.6 ml out of 1.8 ml of 2% lidocaine with 1:80000 adrenaline injection bucally and the same amount infiltration lingually opposite the intended tooth. Group (2) received 1.5 ml out of 1.8 ml of 2% lidocaine with 1:80000 and the remaining 0.3 ml was injected for long buccal nerve anesthesia. Results: In this Study we found 88% patients were pain free and Group-2 94% patients were pain free During extraction of Advance periodontitis of mandibular molars. P-value was 0.138 and it was not < 0.05. So it was not significant. On the other side 103 patients out of 113 were pain free in male and 79 patients out of 87 were pain free in female and 6 patients out of 87 were feeling pain during tooth extraction of advance periodontitis of mandibular molars. P-value was 0.138 and it was not < 0.05. So it was not significant. Conclusion: Infiltration anesthesia for non-vital mandibular molars is effective as a substitute for inferior alveolar block technique. Update Dent. Coll. j: 2020; 10 (1): 13-15